Innovation by proxy – clusters as ecosystems facilitating open innovation - Marita McPhillips (Journal of Entrepreneurship, Management and Innovation)
Open innovation is a concept, whose attributes can be perceived as naturally complementing the proximity-based offer of clusters. The purpose of this paper is to investigate the potential role of clusters as intermediaries of open innovation for cluster members. A literature review and an exploratory study were performed, involving in-depth interviews with experts in the field of innovation and clusters in Poland. This article conceptually links open innovation and clusters, proposes and categorizes roles of clusters as open innovation intermediaries, as well as indicates factors that might affect the successful adoption of this role. Furthermore, it points out that clusters could not only manage and mediate their network of members but also shape and co-create a broader open innovation ecosystem. The findings contribute to a comprehensive understanding of the potential roles of open innovation intermediaries in regard to clusters in the context of transitioning economies. With clusters playing the role of an open innovation intermediary, public support at cluster level could increase the openness to cooperation not only for member companies but all participants in the regional innovation ecosystem.